Peran Orang Tua Dalam Motivasi Belajar Pada Anak Berkebutuhan Khusus (ABK) (Study Kasus pada Anak Autisme) - arofah, nur (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2020)
Parentes’ role is very important in learning motivation to autism child, because the change of child’s growth needs proximity and support from parents. Learning can be told successful if it can create the ways of thinking in new behavior to fulfill child’s need. Many of decreasing in learning motivation to autism child, one of the cause, is the lack of support and care from parents. Because the effort of parents in growing learning motivation to autism child is not maximal, it is caused many parents are busy and too much believe in shadow teacher. There fore the purpose of research to do this research is the role of parents is very important at autism child’s growt, primary in child’s learning motivation. From the research result shows the role of parents in learning motivation to autism child is very important. Especially on subject A, which whom the parents have low role in motivating the learning, because the parents only count on the teacher class and shadow teacher. While the needs in changing of childs growth is from parents different from subject B which whom the parents have completely motivation when giving learning motivation to their children and always watch their growth in academic, social, and communication. Keyword: Learning Motivation, Autism Child.